-2(6)-[3(-7)-2^4 ]
There's a rule called BODMAS for order of operations. B=Brackets, D=Division, M=Multiplication, A=Addition, and S=Subtraction. If you do it in this order you'll get the correct answer.
$\displaystyle -2(6)-[3(-7)-2^4]$
$\displaystyle =-12-(-21-16)$
$\displaystyle =-12-(-37)$
$\displaystyle =25$
We call it "PEMDAS" (Parentheses, Exponents, Multiplication, Division, Addition, Subtraction), or "Please Excuse My Dear Aunt Sally."
You mean this?
$\displaystyle -2(6) - [3(-7) - 2^4]$
(Hint: learn to use LaTex! )
If so,
$\displaystyle \begin{aligned}
-2(6) - [3(-7) - 2^4] &= -2(6) - [3(-7) - 16] \\
&= -2(6) - [-21 - 16] \\
&= -2(6) + 37 \\
&= -12 + 37 \\
&= 25
\end{aligned}$
01